Development and Psychometric Validation of a Multidimensional Scale for Assessing Elementary School Teachers’ Professional Competence - Nur Az Zahra; Herpratiwi; Apri Wahyudi; Muhammad Nurwahidin; Dwi Yulianti (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
This study addresses the gap in the availability of psychometrically tested, context-specific instruments for elementary education. The objective was to develop and validate a specialized, practical, and reliable assessment instrument for school-based performance evaluation. This study contributes to providing a validated and practical instrument specifically designed for elementary school contexts. The study employed a Research and Development (R&D) approach following the ten-stage model of Borg and Gall, including needs analysis, framework development, expert validation, revision, and field testing. The instrument was constructed based on a five-dimensional competency framework and evaluated through expert judgment (content, language, media) and empirical testing involving 120 teachers from ten elementary schools in one subdistrict. Psychometric analysis was conducted using Aiken’s V for content validity, Cronbach’s Alpha for reliability, and user-response questionnaires for practicality. The results showed that all 50 items achieved high content validity (Aiken’s V ≥ 0.80) and excellent reliability (α = 0.888). The practicality level reached 97%, indicating that the instrument is highly feasible, efficient, and effective for real supervisory use. The study concludes that the developed instrument is psychometrically sound and practically applicable, providing principals with an objective and multidimensional tool to support academic supervision and data-driven professional development.